Pengujian Aplikasi Kas Keuangan Menggunakan Katalon - Irpan Kusyadi; Sri Mulyati; Dian Noviyanto; Siti Aisah; Anggit Prastika Setiany (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
The most important thing in making financial improvements in a business is by recording cash receipts and cash disbursements. The output generated from the application is a report on cash receipts and cash disbursements per day, per month and per year, but before the application is published it is necessary to test, if there is a problem when the admin records cash then the risk is very fatal because it is related to joint finance. To solve this problem the author uses a test with Katalon. Katalon Studio is a software used to perform a mechanization test which is extended by Katalon, Inc. The software is built on Selenium's open source mechanization framework, Appium with a dedicated IDE interface for testing web, API, mobile and desktop applications. With Katalon, it is hoped that the cash website will run well and smoothly